The Influence of Price, Product Quality, and Word of Mouth on Purchase Decisions for Gayo Coffee Products - Septi Herawati; Evan Saktiendi; Indah Setiyani (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this study was to determine the effect of price, product quality and word of mouth on purchasing decisions for Gayo coffee products, and the effect of price, product quality and word of mouth simultaneously on purchasing decisions for Gayo coffee. The research method used is a quantitative method. The population in this study are consumers who have purchased Gayo Coffee Products in Jabodetabek. The number of samples is 100 respondents using purposive sampling. To find out the results of this study using analysis tools validity test, reliability test, classic assumption test, multiple linear regression (R2), t test, f test, and determination test. The testing tool used is SPSS 26. The results of this study indicate that partially the Price and Word of Mouth variables have a significant effect on the Purchase Decision of Gayo Coffee Products and the Product Quality variable has no significant effect on the Purchase Decision of Gayo Coffee Products, while simultaneously the price variable, Product Quality, and Word of Mouth have a significant effect on the Purchase Decision of Gayo Coffee Products.